2000
DOI: 10.1023/a:1006357330486
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation, free radical production and antioxidant status in breast cancer

Abstract: Reactive oxygen metabolites (ROMs), including superoxide anion (O2*-), hydrogen peroxide (H2O2) and hydroxyl radical (*OH), play an important role in carcinogenesis. There are some primary antioxidants such as superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) which protect against cellular and molecular damage caused by the ROMs. We conducted the present study to determine the rate of O2*- and H2O2 production, and concentration of malondialdehyde (MDA), as an index of lipid peroxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
219
3
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(244 citation statements)
references
References 46 publications
19
219
3
3
Order By: Relevance
“…Further, the study populations were markedly different from those in the present study in that a significant percentage of subjects were male, many were smokers, and in the Moller study the mean study subject was >3 decades younger than our participants. The levels of oxidative stress in our study group were not as high as has been suggested for breast cancer patients in other studies (40)(41)(42)(43) and may be related to both the fact that our subjects were recruited, on average, just over two years after breast cancer diagnosis and are considered to be consuming relatively healthy diets since the time of breast cancer diagnosis (37). In fact, the plasma carotenoid concentrations observed in the present study sample are generally higher than those observed in the general population, as reflected in National Health and Nutrition Examination Survey III (44).…”
Section: Discussioncontrasting
confidence: 62%
“…Further, the study populations were markedly different from those in the present study in that a significant percentage of subjects were male, many were smokers, and in the Moller study the mean study subject was >3 decades younger than our participants. The levels of oxidative stress in our study group were not as high as has been suggested for breast cancer patients in other studies (40)(41)(42)(43) and may be related to both the fact that our subjects were recruited, on average, just over two years after breast cancer diagnosis and are considered to be consuming relatively healthy diets since the time of breast cancer diagnosis (37). In fact, the plasma carotenoid concentrations observed in the present study sample are generally higher than those observed in the general population, as reflected in National Health and Nutrition Examination Survey III (44).…”
Section: Discussioncontrasting
confidence: 62%
“…In a study of 87 women with breast cancer and 29 control women, Li et al (1999) found that cancer patients had significantly higher levels of lipid peroxidation-related DNA adducts in breast tissue samples than controls. Ray et al (2000) evaluated malondialdehyde (MDA) concentration, an index of lipid peroxidation, along with activity of antioxidant enzymes in 54 breast cancer patients and 42 age-matched controls. Their results showed that irrespective of menopausal status, MDA concentration was significantly elevated in patients with stage II or greater breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of F 2 -isoprostanes in body fluids are elevated by conditions that are thought to be associated with free radical-induced oxidative stress, including smoking (Morrow et al, 1995;Reilly et al, 1996), hypercholesterolemia (Davi et al, 1997;Reilly et al, 1998;Palombo et al, 1999), diabetes (Davi et al, 1999), and acute and chronic alcoholic liver disease Meagher et al, 1999). Recent research suggests a role for oxidative stress in breast cancer (Kumar et al, 1991;Thangaraju et al, 1994;Li et al, 1999;Novak & Woodcroft, 2000;Ray et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Role of free radicals has been proposed in the pathogenesis of many diseases involving different organs such as breast, gastric, colon, multiple myeloma, ovarian and oral cancer (1)(2)(3)(4)(5)(6). Various natural antioxidants available in the cells like glutathione peroxidase (GPx), glutathione S-transferase (GST), superoxide dismutase, catalase, vitamin E and reduced glutathione (GSH) etc.…”
Section: Introductionmentioning
confidence: 99%